The Relationship of Knowledge with the Actions of the Patients of Pulmonary Tuberculosis About the Prevention of Covid–19 in Pulmonary Poly Rumah Sakit Haji Medan 2021 - Zuidah Zuidah (Science Midwifery, 2021)
Covid-19 is the disease caused by corona virus a new type that appears at the end of 2019 the first time in Wuhan, China which is currently causing a pandemic almost all over the world. The main symptoms of the disease Covid-19 such as cough, fever, and shortness of breath. The purpose of this study is to know the relationship of knowledge with the Actions of the Patients of Pulmonary Tuberculosis about the Prevention of Covid-19 in Pulmonary Poly Rumah Sakit Haji Medan 2021. The design of this study is descriptive by using cross sectional study approach. The population in this study are 180 peoples with the techniques of sampling accidental for 2 weeks so that the sample in this study amounted to 30 peoples. The Data used are primary data and data collection of the first by applied a test validity and reliability. The results of this study found that knowledge of the patient of pulmonary tuberculosis about the prevention of Covid-19 the majority is in the category quite are 17 respondents (56,6%), while the actions of the patient of pulmonary tuberculosis about the prevention of Covid-19 the majority are in the category quite are 16 respondents (53,3%). The value of the coefficient of the product moment correlation (rxy) 0,840 are in the category of very strong relationship. Furthermore, the p value significant level of 0.00<0.05, which is means the hypothesis is accepted, it’s mean that there is a relationship of patients’ knowledge of pulmonary tuberculosis about the prevention of Covid-19 in Pulmonary Poly Rumah Sakit Haji Medan in 2021. Concluded that there is a relationship between knowledge and action patients of pulmonary tuberculosis about the prevention of Covid-19. And this research is expected to increase knowledge and action about preventing Covid-19 by applying it in daily life, hopefully can avoid the transmission of Covid-19 for ourselves and others by obeying health protocols and avoiding complications.